Role of next of kin in accessing health records of deceased relatives (BMJ Publishing Group, 2004)

(untitled)
Role of next of kin in accessing health records of deceased relatives Anneke M Lucassen, Michael Parker, Robert Wheeler When potential benefits outweigh harms should clinical geneticists be given access to medical records of dead patients without relatives’ consent? Family history is an important tool used by clinical geneticists to assess risk. Patients’ recollection of family illnesses can sometimes be inaccurate or lack detail. Information obtained through medical records of the patient’s relatives is therefore important. When relatives are alive, the person seeking genetic advice usually asks them for access to their medical records. However, access is more difficult if the relatives are dead. This difficulty is the result of a combination of a lack of clarity in the law and a wariness among hospital departments about releasing information in the light of recent public inquiries and means that hospital departments are often unwilling to allow access to the medical records of deceased patients without consent from their next of kin.We use a fictional case based on real experiences to illustrate the difficulties that this practice can cause in obtaining relevant information for diagnostic and surveillance management of relatives.